Penerapan Terapi Musik untuk Menurunkan Kecemasan pada Pasien yang Akan Dilakukan Percutaneous Coronary Intervention (PCI) - Tallulembang, Abdi; Jumaiyah, Wati; Yunitri, Ninik; Arsianti, Lyana (Journal of Telenursing (JOTING), 2024)
This his study aims to overcome anxiety in CHD patients who will undergo percutaneous coronary intervention (PCI). The method used was random sampling with a sample of 12 CHD patients who were going to undergo PCI. This sample size was obtained from calculations using G-Power version 3.1.9.4. The research results showed that the characteristics of the participants in the EBNP were an average age of 48.4 years (12.3%), male 9 (75.0%), Muslim 7 (58.4%), high school education 5 (41.7%), married status 11 (91.7%), BPJS health insurance for retired military personnel 5 (41.7). The results of the T-Test analysis or comparison test of state anxiety inventory and trait anxiety inventory before and after being given music therapy showed a P value of 0.000. In conclusion, music therapy has a significant effect on reducing anxiety in patients with coronary heart disease who will undergo PCI or percutaneous coronary intervention. Keywords: Anxiety, CHD, Music therapy